Fundamental study of a strategy for Solving Disordered Crystal Structures from PXRD Data by Direct-Space Techniques. - Gin , Keat Lim

(untitled)
Phenomenon of structural disorder in materials· has become an increasingly popular field of investigation for researchers studying the relation between thermodynamic stability and structural properties of crystals.